CONSENT IN A TRAFFICKING PARADIGM: EXPLORING THE CONFLATION BETWEEN SEX TRAFFICKING AND VOLUNTARY SEX WORK (UUM Journal of Legal Studies, 2023)
This article explores the notion of consent inthe trafficking paradigm and the conflation of voluntary sex work and sex trafficking in Malaysia. The article argues that because consent of a trafficked victim is irrelevant inthe context of international law, the authorities tend to conflate voluntary sex work with trafficked sex work. This obstructs a clear definition of trafficking and places women in precarious positions. The article also aims to evaluate the approaches in protecting victims through raids and rescue operations, shelter detention, andjudicial processes in the respective states in the country. The article will demonstrate that while women areuniquely positioned to be a part of the fight against sex trafficking through their access to information, their consent to be pa.rt of the process in tackling sex trafficking has been ignored, negated, and disregarded throughout the anti-trafficking regime. Such practices are seen as violating women' s fundamental rights and fosters distrust between trafficked women and the authorities. It also demonstrates the failure of the government in addressing human trafficking issues.